Studi Transformasi Gelombang Di Pesisir Timur Pulau Tarakan Dengan Metode Shore Protection Manual (SPM 1984) Untuk Rencana Awal Bangunan Pengaman Pantai - Hidayat, Wahyu; Utomo, Edy; Amiruddin, Aswar (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
Tarakan Island is a part of North Kalimantan Province. The coastline of Tarakan Island is long + 28 km. Some areas have sandy beaches that slope towards the sea. This area is known as Amal Beach. On the coast In Amal Baru, there has been damage to the coastline caused by abrasion with a level of damage reaching 66,67%, which was heavily damaged and 33,33% was moderately damaged. The rate of change in this coastline is classified as 2-5 m/year.. There is damage in the Amal Baru beach area caused by abrasion. Therefore, protection is needed along the Amal coast in the form of beach safety buildings. However, in planning coastal safety buildings. Sea waves are one of the important parameters that need to be taken into account. Direct collection of ocean wave data has a high level of technical difficulty and expensive operational costs. This can be overcome by conducting wave forecasting, so that you can find out wave characteristics such as height, direction and duration of the wave. In this research, the SPM (Shore Protection Manual) method was used to calculate wave forecasting based on wind data over a 10 year period obtained from ECMWF (European Center for Medium-Range Weather Forecasts). Data from forecasting results using the SPM method obtained a maximum wave height value of 2.10 meters with a period of 7,63 seconds which occurred in 2016. Meanwhile, the predicted wave height in the next 25 years using the Weibull method was 2,34 meters with a period of 7,74 seconds. The high value of breaking waves in the next 25 years is 1,69 meters and occurs at a depth of 4.03 meters with a wave incident angle of 28,90O.